2014
DOI: 10.1089/dia.2013.0251
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Signs of Foot Infection in Diabetes Patients Using Photographic Foot Imaging and Infrared Thermography

Abstract: Diagnosis of foot infection in patients with diabetes seems valid and reliable using photographic imaging in combination with infrared thermography. This supports the intended use of these modalities for the home monitoring of high-risk patients with diabetes to facilitate early diagnosis of signs of foot infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 30 publications
(45 reference statements)
0
47
0
1
Order By: Relevance
“…By combining photographic and temperature assessments using a parallel strategy, the sensitivity was 61‐70% and specificity 79‐80%, resulting in positive and NPVs of 80‐83% and 53‐65%, respectively. Intra‐observer agreement between photographic assessments was good (Cohen κ = 0.77) and moderate (0.52) between the two observers …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…By combining photographic and temperature assessments using a parallel strategy, the sensitivity was 61‐70% and specificity 79‐80%, resulting in positive and NPVs of 80‐83% and 53‐65%, respectively. Intra‐observer agreement between photographic assessments was good (Cohen κ = 0.77) and moderate (0.52) between the two observers …”
Section: Resultsmentioning
confidence: 95%
“…Summary of the literature : The validity and reliability of assessing DFI using photographic foot imaging and infrared thermography were reported in a convenience sample of 38 consecutive patients with diabetes who presented with a foot infection or were admitted to an inpatient clinic with a foot‐related complication. The authors suggested that foot infection could be suspected on the basis of a temperature difference between the affected and the unaffected foot of greater than 2.2°C, which they defined as a “hotspot.” Two independent observers compared “live” clinical assessment using the PEDIS classification with photographs (assessed for the presence of erythema and ulcers) taken at study inclusion and at 2 and 4 weeks later. The specificity of photographs for the diagnosis of infection was greather than 85%, but the sensitivity was greater than 60%.…”
Section: Resultsmentioning
confidence: 99%
“…While two studies suggest that with photographic foot imaging diabetic foot ulcers can be reliably assessed, the diagnosis of abundant callus proves to be moderately reliable and the studies were too small to reliably assess other important signs such as blisters, fissures, and erythema. The same research group showed that the combination of photographic imaging and infrared thermography improves accuracy over a single modality alone in the diagnosis of diabetic foot infection . This is the first time that home‐monitoring approaches for the early diagnosis of foot infection have been presented.…”
Section: Discussionmentioning
confidence: 90%
“…Good feasibility of using the photographic foot imaging device in the home environment was also shown: patient adherence was high, referrals based on photographic assessment justified, and perceived usability was good . The same authors also showed in a cross‐sectional study that diagnosis of foot infection is valid and reliable using photographic imaging in combination with infrared thermography, taking clinical diagnosis as reference (sensitivity >60%, specificity >79%), and better than with using each modality on its own . In two case series, Foltynski et al assessed the feasibility of at‐home use of the TeleDiaFoS system for ulcer monitoring, and included: total number of assessed ulcer pictures, the length of the monitoring period, and change in ulcer area after four and 12 weeks follow‐up .…”
Section: Resultsmentioning
confidence: 99%
“…Measures of agreement were described in two studies. Bravo‐Molina et al showed a κ coefficient of 0.574, and Hazenberg et al of 0.44, both indicating moderate agreement between raters who evaluated the same ulcers.…”
Section: Resultsmentioning
confidence: 97%